Perencanaan Pembelajaran Matematika di SMK Negeri 6 Padang (Modul Ajar, Assesment (Penilaian), Program Pengayaan, Remedial, Olimpiade, LKPD, Buku Pegangan Guru dan Buku Pegangan Siswa - Astri Sukriani Piliang; Nita Putri Utami (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study aims to analyze and describe mathematics learning planning at SMK Negeri 6 Padang, specifically including the preparation of Teaching Modules, implementation of assessments, and enrichment and remedial programs. Furthermore, this study also examines the role and implementation of mathematics Olympiad preparation, the use of Student Worksheets (LKPD), and the availability and utilization of Teacher's Handbooks and Student Handbooks. A qualitative approach with a case study method was used in this study. Data were collected through observation, in-depth interviews with mathematics teachers, and analysis of documents related to learning planning. The results of the study indicate that mathematics learning planning at SMK Negeri 6 Padang has referred to the applicable curriculum. The Teaching Modules are systematically arranged covering learning objectives, materials, activities, and evaluations. Assessments are carried out formatively and summatively, using various techniques to measure student understanding. In addition, the school also implements remedial programs for students who have not achieved learning completion and enrichment programs for students who have mastered the material, including preparation for the Olympiad. LKPD has been shown to facilitate students' understanding and active participation, while the Teacher's Handbook and Student Handbook are important resources. However, several challenges were found in the implementation, such as time constraints in compiling varied teaching modules and optimizing the use of assessment results for continuous learning improvements. So it ca be concluded that learning planning is effective, namely . Therefore, it is recomended that further training is needed to improve the quality of independent curriculum-based learning planning